The effects of angiotensin-converting enzyme inhibitors on peritoneal protein loss and solute transport in peritoneal dialysis patients (Clinics, 2012)
OBJECTIVE: The objective of this study was to examine the effects of angiotensin-converting enzyme inhibitors on peritoneal membrane transport, peritoneal protein loss, and proteinuria in peritoneal dialysis patients. METHODS: Fifty-four peritoneal dialysis patients were included in the study. The patients were divided into two groups. Group 1 (n = 34) was treated with angiotensin-converting enzyme inhibitors. Group 2 (n = 20) did not receive any antihypertensive drugs during the entire follow-up. Eleven patients were excluded from the study thereafter. Thus, a total of 30 patients in Group 1 and 13 patients in Group 2 completed the study. We observed the patients for six months. Group 1 patients received maximal doses of angiotensin-converting enzyme inhibitors for six months. Parameters at the beginning of study and at the end of six months were evaluated. RESULTS: At the end of six months, total peritoneal protein loss in 24-hour dialysate effluent was significantly decreased in Group 1, whereas it was increased in Group 2. Compared to the baseline level, peritoneal albumin loss in 24-hour dialysate effluent and 4-hour D/P creatinine were significantly increased in Group 2 but were not significantly changed in Group 1. A covariance analysis between the groups revealed a significant difference only in the decreased amount of total protein loss in 24-hour dialysate. Proteinuria was decreased significantly in Group 1. CONCLUSION: This study suggests that angiotensin-converting enzyme inhibitors reduce peritoneal protein loss and small-solute transport and effectively protect peritoneal membrane transport in peritoneal dialysis patients.